Sensitivity of Vibrio parahaemolyticus, V. vulnificus and V. harveyi Against Chloroxylenol (4-Chloro-3,5-dimethylphenol , C8H9ClO) Antiseptic and Pine Oil Disinfectant - Subagiyo Subagiyo; Ervia Yudiati; Nuril Azhar; Rabia Alghazeer (Jurnal Kelautan Tropis, 2020)
Vibrio spp. genus is known as a marine indigeneous bacteria. Vibrio parahaemolyticus, V. vulnificus and  V. harveyi are pathogenic Vibrio. This study aims to assess the sensitivity of three Vibrio species (V parahaemolyticus, V. vulnificus and V. harveyi) isolated from shrimp pond against two type of disinfectant with different active compound namely Chloroxylenol (4-Chloro-3,5-dimethylphenol, C8H9ClO) and pine oil. The assessment was done by Kirby-Bauer disk diffusion methods in Zobell agar media with two different concentration (10 and 100 ppm) and replicated in three times. Sensitivity of Vibrio spp. was analized based on the inhibition zone activity produced by disinfectant. Results showed that sensitivity of Vibrio spp. against disinfectant Chloroxylenol 4.8% at 100 ppm were higher than 10 ppm. The increment of V parahaemolyticus was 182 %, V. vulnificus was 47 % and V. harveyi was 43 %, respectively.  Susceptibility of antiseptic with Chloroxylenol 4.8% at 100 ppm was arised to 152 % (V. parahaemolyticus), 43 % (V. vulnificus) and 31 % (V. harveyi) when compared to 2.5% pine oil disinfectant. It can be concluded that Chloroxylenol  4,8 % active compound and pine oil were able to inhibit the Vibrio spp. growth.